Study of Nitrogen Assimilation with Molybdenum and Rhizobium for Higher Yield of Green Gram (Vigna radiate L.) - Maity, Utpal; Roy, Bidhan; Mutum, Bigyananda; Laya, Bijoy Basanta; Vennupusa, S. S. Reddy; Poddar, Sagnik; Barman, Bipul (International Journal of Economic Plants, 2025)
A field experiment was conducted during the rabi season (October–March) in 2018–19 at experimental farm of Bidhan Chandra Krishi Viswavidyalaya, Mohanpur, Nadia, West Bengal with four varieties of green gram (Vigna radiate L.), namely, B-1, B-27, Sona and Chaitali to assess the effect of differences in treatments of seeds on growth, physiological and economic parameters. For this purpose, the seeds were treated in combination with Rhizobium sp. and Molybdenum separately prior to sowing to find out the effect of treatment on nitrogen assimilation on yield and quality seed production compared to control (non-treated). This experiment was expected to identify the best performing cultivars (physiological and economic parameters) among other selected alternative cultivar varieties. The results showed a positive effect on the length of root and shoot, accumulation of dry matter, no. of nodule formation, carbohydrate synthesis, etc. Besides, the treatment with Rhizobium Sp. and Molybdenum had found to promote higher level of the protein content in seed. Among four selected cultivars, Sona cultivar had demonstrated the best results with inter alia maximum yield (17.24 q ha-1) which was 48% higher than control. Findings indicate that the combined treated seeds could enhance the growth of different yield contributing parameters which, in turn, helped increase production and productivity of green gram over control. Besides, it would also help the farmer while selecting the best cultivars of green gram in the area of study for economic advantage and welfare of the cultivators.